2017
DOI: 10.1016/j.rmed.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Sputum microbiota in severe asthma patients: Relationship to eosinophilic inflammation

Abstract: Patients with asthma have an altered airway microbiota, with specific bacteria associated with severe asthma and the eosinophilic inflammatory phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 27 publications
(33 reference statements)
6
69
1
Order By: Relevance
“…The reason for this is that the eosinophilia in sputum on tissue or luminal appears to be the most accurate and clinically relevant. 24 There was no statistical difference in lung function parameters, which may be attributed to the control of asthma in most children before AIT, but PC20 significantly improved after AIT as we found in another article. 25 In this study, we analyzed the relationship between serum parameters before AIT and AIT efficacy, which provided a reference for selecting the appropriate patients for AIT.…”
Section: Discussionsupporting
confidence: 57%
“…The reason for this is that the eosinophilia in sputum on tissue or luminal appears to be the most accurate and clinically relevant. 24 There was no statistical difference in lung function parameters, which may be attributed to the control of asthma in most children before AIT, but PC20 significantly improved after AIT as we found in another article. 25 In this study, we analyzed the relationship between serum parameters before AIT and AIT efficacy, which provided a reference for selecting the appropriate patients for AIT.…”
Section: Discussionsupporting
confidence: 57%
“…Again, this might be related to the effect of corticosteroids, which by suppressing immunity would enhance the growth of diverse microbiota. However, in other studies, no significant differences in bacterial diversity were found between asthma patients and healthy controls . Other studies showed that asthmatic patients had lower airway and gut microbiome diversity when compared to healthy controls …”
Section: Latest Insights Into Microbial Dysbiosis and Asthma Phenotypmentioning
confidence: 78%
“…Three studies have reported that neutrophilic asthma patients had lower sputum bacterial richness and diversity and showed higher abundances of Proteobacteria phylum especially Moraxella and Haemophilus compared with non‐neutrophilic, eosinophilic or paucigranulocytic asthma phenotypes . In contrast, eosinophilic asthma patients had higher sputum abundances of Actinobacteria phylum especially Actinomycetaceae family compared with non‐eosinophilic or neutrophilic asthma patients . The microbial dysbiosis observed between different asthma phenotypes has driven some research groups to phenotype cluster their patients based on asthma clinical and biochemical characteristics before exploring microbial dysbiosis between these phenotypes.…”
Section: Latest Insights Into Microbial Dysbiosis and Asthma Phenotypmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also proved that colonization with Clostridium coccoides (ranked 3rd in the list) and Bacteroides (ranked 7th in the list) at 3 weeks were associated with positive predictors of asthma at age 3 (Carl et al, 2008(Carl et al, , 2011. In addition, the abundance of Firmicutes (ranked 2nd in the list) and Enterobacteriaceae (ranked 5th in the list) were higher in severe asthmatics compared with non-asthmatic people, while Actinobacteria (ranked 4th in the list) and Lachnospiraceae (ranked 9th in the list) with lower proportion (Marri et al, 2013;Ciaccio et al, 2015;Zhang et al, 2016;Li et al, 2017). Moreover, Huang et al (2018) found that Lactobacillus (ranked 6th in the list) can reduce asthma severity and improve asthma control, which is beneficial to children with asthma.…”
Section: Asthmamentioning
confidence: 98%